The Effect of Teachers' Leadership and Communication Ability on Students' Learning Motivation in Class VIII of SMP Negeri 13 Pematang Siantar - Erlina Br Manurung; Binsar Tison Gultom; Paulina H.N. Sirait (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine how much influence the teacher's leadership and communication skills have on the learning motivation of class VIII students of SMP Negeri 13 Pematang Siantar. Quantitative type research. The sampling technique in this study was a total sampling technique of 95 respondents. Data collection techniques using interviews, questionnaires (questionnaire) and documentation. The data obtained is questionnaire data. The instrument test used the Classical Assumption test and the hypothesis test used was the t partial test (T test), F simultaneous test (F test), and the coefficient of determination test (R^2). The results of the research and processing of partial test data (t test) show that tcount is 4,601 > ttable 1,98609 and the significance is 0,000 <0,005 so it can be concluded that the quality of teacher leadership has a significant effect on the learning motivation of class VIII students of SMP Negeri 13 Pematang Siantar. From the partial test (t test) the teacher's communication ability variable (X2) has a significant effect on student learning motivation with tcount 2,912 > 1,98609 and its significance is 0,005 = ttable 0,005 so it can be concluded that the suitability of teacher communication skills has a significant effect on student motivation in class VIII SMP Country 13 Pematang Siantar.